Assisted Tip Sonication Approach for Graphene Synthesis in Aqueous Dispersion - Ahmed F. Ghanem (Biomedicines, 2018)
Graphene (G) is a newcomer material that holds promising properties for many applications. The production of high quality G with a good yield is a long-standing goal for many researchers. This work emphasizes synthesis of dispersed graphene nanoplatelets (DGP) through aqueous dispersion technique in surfactant/water solution with the aid of tip sonication. A chemical method was also used to prepare graphene oxide (GO) and reduced graphene oxide (RGO) for comparison. Elemental analysis revealed the C:O ratio to be 12:1 for DGP but much lower for other graphene structures. Optical characterization of DGP, GO and RGO with UV and Raman spectroscopy confirmed the ideal structure of DGP. Moreover, X-ray diffraction (XRD) revealed the amorphous structure of DGP. Transmission electron microscope (TEM) imaging showed that DGP was composed of a few flat layers, unlike the wrinkled and partially bent multilayered G. Topological study of the DGP surface with scanning electron microscope (SEM) depicted its rough surface with (ra) value of 35 nm, as revealed using an atomic force microscope (AFM). Electrochemical measurements confirmed the higher conductivity of DGP over graphene prepared by chemical method due to lack of structural defects. Its perfect structure facilitates the mobility of charge carriers that makes it preferable in optoelectronic applications.